Advancing Coherent Theories of Change in Special Education Teacher Education Research: A Response to the Special Issue on the Science of Teacher Professional Development. (May 2018) - Brownell, Mary T.; Leko, Melinda M.
In this article, the authors provide a response to the special issue The Science of Teacher Professional Development: Iterative Design Studies Across Content Areas. In doing so, they present the framework of professional development (PD) enactment developed by Mary Kennedy and apply it to the three studies highlighted in this special issue. They also present implications regarding the advancement of coherent theories of change within special education teacher education research.